PERANCANGAN DIGITALISASI PELAYANAN ADMINISTRASI AKADEMIK JURUSAN TEKNIK ELEKTRONIKA BERBASIS ANDROID - Sandy Putra Effendi; Elfi Tasrif (Universitas Negeri Padang, 2019)
The design of this application describes how to digitize the academic administration services of the Android-based Electronics Engineering department. The purpose of designing this application is to improve aspects of departmental administrative services and provide satisfaction to students in higher education, especially the Department of Electronics Engineering, Faculty of Engineering, Padang State University. Android-designed application that uses the Java programming language and developed using PHP and MySQL as database design and data management. The application is also designed based on client-server. The design stages in this application, namely system requirements analysis, system design, code making and testing. The method used in the design is the waterfall method which consists of needs analysis, design, implementation and testing. The interface design consists of the home page, login page, service input page, update and delete service pages and service pages received. Keywords: Administrative Services Department, Android